Random impact force localisation enabled by the weighted reference database method - Binbin Qiu; Siqi Liu; Weidong Li; Chunhua Feng; Yu Zhu; Haoran Liu (Scientific Reports)
Abstract The mechanical properties of an engineering structure can be substantially influenced by a random impact force (RIF), which may compromise the integrity and safety of the structure. Nevertheless, accurately localising the RIF applied to a structure presents a significant challenge. To address this issue, this study introduces a novel method known as the weighted reference database method (WRDM). Its innovations are reflected in three aspects: (i) constrained by the sparse construction of a reference database, bicubic interpolation is utilised to increase the reference impact point density and improve the localisation accuracy; (ii) a weighted random impact localisation framework is constructed, in which a cosine distance variant is chosen as the weight to further improve the localisation accuracy; and (iii) to overcome the region limitation of interpolation, the boundary range of the WRDM is extended. Experiments on a suspended rectangular plate were conducted to validate and demonstrate the effectiveness of the WRDM in terms of localisation accuracy. The experimental results indicate that the average absolute error of the method is 16.67 mm (the interpolation interval size is 2 mm and the prioritisation point number (PPN) is 108), and its localisation accuracy is higher than that of previously published methods (21.54 mm for PRMCSM; 20.80 mm for the hybrid method).